2017
DOI: 10.1210/en.2017-00768
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal Development of Gonadotropin-Releasing Hormone Neuron Activity Is Altered by Sex, Age, and Prenatal Androgen Exposure

Abstract: Gonadotropin-releasing hormone (GnRH) neurons regulate reproduction though pulsatile hormone release. Disruption of GnRH release as measured via luteinizing hormone (LH) pulses occurs in polycystic ovary syndrome (PCOS), and in young hyperandrogenemic girls. In adult prenatally androgenized (PNA) mice, which exhibit many aspects of PCOS, increased LH is associated with increased GnRH neuron action potential firing. How GnRH neuron activity develops over the prepubertal period and whether this is altered by sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 75 publications
9
55
1
Order By: Relevance
“…Although LH is low throughout prepubertal life, GnRH neurons are highly active throughout this period (58) and undergo dramatic morphological and synaptic plasticity prior to pubertal onset (33). Two very recent reports out of the Moenter laboratory have reported that both GnRH neuron firing activity (58) and GABAergic transmission to GnRH neurons (59) are present at 1 week of age and peak around 3 weeks of age, corresponding closely to the time point investigated here. Berg et al have shown that GABAergic inhibitory post-synaptic currents (IPSCs) in PNA females are higher than controls at 3 weeks of age, lending support to our anatomical findings.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although LH is low throughout prepubertal life, GnRH neurons are highly active throughout this period (58) and undergo dramatic morphological and synaptic plasticity prior to pubertal onset (33). Two very recent reports out of the Moenter laboratory have reported that both GnRH neuron firing activity (58) and GABAergic transmission to GnRH neurons (59) are present at 1 week of age and peak around 3 weeks of age, corresponding closely to the time point investigated here. Berg et al have shown that GABAergic inhibitory post-synaptic currents (IPSCs) in PNA females are higher than controls at 3 weeks of age, lending support to our anatomical findings.…”
Section: Discussionsupporting
confidence: 68%
“…Berg et al have shown that GABAergic inhibitory post-synaptic currents (IPSCs) in PNA females are higher than controls at 3 weeks of age, lending support to our anatomical findings. However, they also report that GnRH firing frequency and response to GABA application was unexpectedly blunted in PNA mice when compared with control females (58,59). It is tempting to speculate that increased GABAergic synaptic contact and synaptic transmission would be coincident with increased GnRH neuron activity even in the juvenile period.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we reported that pituitary Amhr2 expression is also higher in female rats during this developmental period [16]. A higher GnRH neuron activity has recently been reported in infantile 2- to 3-week-female mice as compared to males [70]. Based on our present study, we can hypothesize that this contributes to dimorphism of pituitary Amhr2 expression and hence to the sexually dimorphic secretion of FSH during infancy.…”
Section: Discussionsupporting
confidence: 77%
“…In the pituitary, AMH binds to AMHRII to increase FSH synthesis and secretion, specifically during the infantile period in the female rat (Garrel et al 2016). It would be of interest to specify the contribution of ovarian AMH to the transient increase in both GnRH neuron activity and gonadotropin levels observed during the infantile period (Dulka & Moenter 2017, François et al 2017.…”
Section: :2mentioning
confidence: 99%